DIGITAL MARKETING CHANNELS IN MICRO, SMALL AND MEDIUM ENTERPRISES IN SURABAYA CITY - Ricky Angga Ariska; Fadilla Purwitasari; Renta Yustie (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This research was conducted to determine the extent to which digital marketing was adopted by Micro, Small & Medium Enterprises (MSMEs). In addition, it also analyzes the factors that influence the use of digital marketing channels in MSMEs. This study is qualitative research that explores individual perceptions. The data collection method used structured interviews. The object of this research is MSMEs in the city of Surabaya. Determination of the research sample using the purposive sampling technique. Digital marketing has a positive impact on the marketing activities of MSMEs. The perceived positive impact is in terms of flexibility and efficiency. With digital marketing, marketing activities can be done anywhere and without bringing products to be shown to consumers. This is very helpful for MSMEs in their marketing activities. Digital marketing can also reduce the costs incurred for marketing activities. However, digital marketing requires an internet connection, and respondents stated that the expenses incurred were for internet quotas or internet subscriptions.